2012
DOI: 10.1016/j.ijgo.2012.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of misoprostol-only and combined mifepristone-misoprostol regimens for home-based early medical abortion in Tunisia and Vietnam

Abstract: Mifepristone plus misoprostol is significantly more effective than misoprostol-only for early medical abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…[15][16][17]19,20 Our study demonstrates that the mifepristone-misoprostol regimen can be provided with existing staff and equipment in menstrual regulation services in Bangladesh. Midlevel providers assisted in the eligibility screening and postabortion follow-up, especially in the phase-two sites.…”
Section: Discussionmentioning
confidence: 78%
“…[15][16][17]19,20 Our study demonstrates that the mifepristone-misoprostol regimen can be provided with existing staff and equipment in menstrual regulation services in Bangladesh. Midlevel providers assisted in the eligibility screening and postabortion follow-up, especially in the phase-two sites.…”
Section: Discussionmentioning
confidence: 78%
“…Gestational age-specific outcomes were reported in the literature for 505, 129, and 49 women with pregnancies 49 days or less, 50-56 days, and 57-63 days of gestation, respectively. All studies used a regimen with 200 mg mifepristone and 800 micrograms misoprostol buccally 13,[17][18][19][20] except for one study that used 200 mg mifepristone and 400 micrograms misoprostol buccally. 21 Clinical outcomes for one study, which included women who were treated but were actually not pregnant, were recalculated to include only women who were pregnant.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the side-effect profile of both regimens is comparable, and regimens with buccal misoprostol have been shown to be well tolerated and acceptable to participants. 18,19,21,24 Despite the presence of data supporting buccal misoprostol in medical abortion, there are still gaps in the literature, specifically with use 24 hours after mifepristone. Based on the available literature, the overall efficacy of regimens with a 24-hour interval There is also a paucity of data on the actual time interval at which women actually administer misoprostol when instructed to use buccal misoprostol in a 24-to 48-hour window after mifepristone.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed the rates of MRM success 93-98% (17)(18)(19)(20)(21). A study by Alam A et al 2013, in Bangladesh used 200 mg of mifepristone followed by 800 mcg of misoprostol found 93% women evacuated the uterus without surgical intervention and overall 92% were satisfied with use…”
Section: Fig 2: Patients Complains After Taking Mrm Kitmentioning
confidence: 99%